Assessment of Village Readiness for Electronic Citizen Complaint Services (e-AduMas) Using COBIT 4.1 - Ferdiansyah, Doddy; Majapahit, Sali Alas; Muttaqin, Muhammad Fadli (Universitas Bina Darma, 2023)
The objective of this study is to investigate the implementation of the electronic community complaint service, known as e-AduMas, in villages utilizing SMS Gateway and GSM network technologies. The research aims to evaluate both the technological readiness of village offices using COBIT 4.1 and the community's acceptance of the e-AduMas system. The study employs a comprehensive research methodology that includes the analysis of community needs, the design of the e-AduMas system, the development of an integrated SMS Gateway application with the village government platform, and field testing involving active participation from the village community. Data will be collected through surveys, interviews, and observations to assess the level of implementation success, user response, and technical feasibility. The anticipated outcomes of this research include practical guidance for other villages looking to construct similar systems to enhance citizen participation in local governance. This study is poised to make a significant contribution to the application of technology in village governance, specifically in the development and utilization of the e-AduMas service. The findings of this research are expected to provide valuable insights for strengthening citizen engagement in local governance through innovative technological solutions.